Estudios de desarrollo económico local - Juárez Mancilla, Judith (Corporación Universitaria Americana, 2022)
Latin America has been hit by countless social, political and economic conflicts throughout its history, which have unleashed problems related to violence and social inequality, job creation, and attractiveness to investors. When these aspects manage to be regulated and transformed in favor of the economic and social development of a territory, society can approach a State that favors welfare conditions. However, the high challenges that a national government may encounter on this path are almost impossible to overcome. Even so, an alternative way that some communities and cities have opted for has been to turn their gaze inward, that is, based on their territory, their local culture and effective citizen participation, routes can be identified that dynamize productivity and competitiveness in a sustainable manner. Each of the actors involved in these practices must recognize the potential and real resources of the territory and the community in order to be used to strengthen it. The last few years, more specifically since the emergence of the Covid-19 pandemic contingency, brought high threats to the growth, development and welfare of countries, which resulted in major economic and social challenges that each government is still trying to overcome.